2002
DOI: 10.1021/ja0256919
|View full text |Cite
|
Sign up to set email alerts
|

The Cobalt-Catalyzed Alternating Copolymerization of Epoxides and Carbon Monoxide:  A Novel Approach to Polyesters

Abstract: The metal-catalyzed synthesis of polyolefins, polyketones, and polycarbonates is well-known in academia and is already successfully applied in industrial processes. Still missing, however, is the metal-catalyzed synthesis of aliphatic polyesters, as one of the most important biodegradeable polymer families. We report here on the cobalt-catalyzed alternating copolymerization of propylene oxide and carbon monoxide, affording atactic and isotactic polyhydroxybutyrates (PHB). The postulated mechanism is supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 14 publications
0
97
1
1
Order By: Relevance
“…[16] A mechanistic proposal for the occurrence of multiple, alternating PO/CO insertions starts with the cleavage of the cobaltÀacyl bond in 5 by pyridine to give an acylium cation and tetracarbonyl cobaltate (6, Scheme 4). [17][18][19][20] Interaction of the Lewis-acidic acylium cation with PO (7) activates the 4 ] À (6 ! 7).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[16] A mechanistic proposal for the occurrence of multiple, alternating PO/CO insertions starts with the cleavage of the cobaltÀacyl bond in 5 by pyridine to give an acylium cation and tetracarbonyl cobaltate (6, Scheme 4). [17][18][19][20] Interaction of the Lewis-acidic acylium cation with PO (7) activates the 4 ] À (6 ! 7).…”
Section: Resultsmentioning
confidence: 99%
“…[3] Our initial forays into that field surprisingly revealed that besides the ring opening of b-butyrolactone, there is a direct alternating copolymerization reaction of propylene oxide and CO to give PHB. [4][5][6] This direct copolymerization reaction, which combines a Lewis acid (LA) induced epoxide ring opening process with a metal centered CO insertion, was initiated from 2 (Scheme 2), [7] simply by adding pyridine. However, a detailed mechanistic understanding, including the identification of the catalytically important intermediates, was lacking.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations